O Ensino por Unidades Didáticas e a retomada da Pedagogia Herbartiana no Colégio Nova Friburgo da Fundação Getúlio Vargas (CNF/FGV) - Santos, Pablo Silva Machado Bispo dos (Educação On-line, 2006)
The present study had had as principal objective to throw a new look on the Unidades Didáticas teaching method, developed on the Colégio Nova Friburgo of the Fundação Getúlio Vargas (CNF/FGV), expert as a experimental school created by the private initiative. For so much, looked for to investigate such object through the study of the institutional memory of CNF, examining two documental sources in whose materiality such memory had presented concret way (two books edited by FGV about CNF and former-students’ testimonies and former-teachers of CNF). At the end of the present study it was possible to capture elements of a traditional pedagogy and of a traditionalistic speech and patrimonialist that were presented for besides the ideas of pedagogic innovation and administrative competence presents in the analyzed documents.